Social Women Share: Technology as an Enabler - Irene Kamberidou; Labovas, Manolis (Reflections on Women in Entrepreneurship and ICT / A Reader, 2012)
The concept of Social Media is at the top of the agenda of many entrepreneurs, business executives and decision makers today. This paper examines the new media and digital culture which has become an important part of our daily activities, using the social network perspective, a theoretical concept as used in the social and behavioural sciences. This theoretical perspective allows us to identify the dynamics of social networks: the concept of social media today, for many a new and stimulating environment and for others a social space that evokes feelings of frustration or fear of losing touch with the real world. Are women equipped to thrive in this digital age and especially in this virtual environment? In examining current research findings on social women, new models of work, levels of engagement, transformational leadership styles and women entrepreneurs that have been de-mystifying the world of social media through the lens of their own experiences, this paper argues that women enjoy a slight edge over their male counterparts and that today’s business climate is more inviting for aspiring women entrepreneurs. The bottom line is that social women are doing what most women do "naturally", namely creating relationships, community, connections and support. Isn’t that what social networking is all about? Social women share content in multiple ways and working online has been a financial windfall for many, including stay at home moms and homemakers. Finally, this paper presents tips and advice from successful women entrepreneurs who tell how they have been using social media to excel in their careers and balance their career/family/personal lives.   Keywords: new media, social media, social networking, technology as an enabler, integrating a gender perspective, “feminine” skills and leadership qualities